Disaster Information on Mobile Application in Indonesia Using Sequential Search Algorithms Based On Android - Bachtiar, Dimas Agung; Pahlevi, Omar; Santoso, Tri (Politeknik Ganesha Medan, 2019)
Indonesia has 28 regions in the Republic of Indonesia Archipelago which are declared as areas prone to tectonic earthquakes, volcanoes and tsunamis. Among these are NAD, North Sumatra, West Sumatra, Bengkulu, Lampung, Banten, Central Java, and DIY in the south, East Java in the south, Bali, NTB, and NTT. Based on these facts, it can give an idea that the South East Java Province in particular has a high level of vulnerability when compared to other islands, when viewed from the total population density. Disasters can occur anytime and anywhere so people need to increase awareness, awareness, and preparedness, which is most at risk during the emergency response phase, where in that phase the situation is very conducive and the increasing hoaxes about data and information on disasters that spread in the community, along with the development of technological advancements, we need a mobile application that can provide the latest data and information routinely in the community. Referring to the design of mobile application designs that have been designed, in this study using the sequential algorithm method. With the sequential algorithm in this design, users can easily use this Android-based disaster information application, just by entering the keywords in the year of the disaster event, the location will be searched. The purpose of making this mobile application is to be able to provide data and information about disasters in Indonesia to all elements of society effectively and efficiently.